PENGGUNAAN TEKNOLOGI INFORMASI DAN UNDANG-UNDANG INFORMASI TRANSAKSI ELEKTRONIK - Silvester Magnus Loogman Palit; Tumian Lian Daya Purba (LPPM Uncen, 2023)
This service will be carried out under the title Application of Science and Technology Use of Information Technology and Electronic Transaction Information Law at YPPK Taruna Darma Kotaraja High School, activities that will be carried out to partners due to lack of student knowledge about the use of information technology and Electronic Transaction Information Laws, which now have many children students are not wise in using information technology media and do not violate the law through social media. The obstacle is that students do not understand and master the use of information technology and the Electronic Transaction Information Law so that with the expertise possessed by servants, they can implement the science and technology. The method of implementing this service is carried out by applying science and technology and providing assistance to partners. The output of this service is that partners can understand the use of information technology and the Electronic Transaction Information Law.Keywords: Technology; Information; Law; ITE